THE CONSTRUCTION OF THE AK-SARAY PALACE DURING THE REIGN OF AMIR TEMUR AND ITS POLITICAL AND CULTURAL SIGNIFICANCE (American Journal of Research in Humanities and Social Sciences, 2026)
This article provides a comprehensive analysis of the construction process, architectural design, and political, military, and cultural significance of the Oqsaroy majmuasi built during the reign of Amir Temur. The study aims to examine the palace not only as an architectural monument but also as a complex socio-political institution that reflects the state-building strategies and ideological foundations of the Timurid Empire.The research is based on a combination of historical-analytical and comparative methods, utilizing both primary historical sources and modern scholarly literature. Particular attention is given to the technological aspects of construction, including foundation engineering, water supply systems, and structural organization. The findings reveal that the Ak-Saray Palace was constructed using advanced engineering techniques for its time, such as layered foundations with water stabilization, long-distance water transportation systems, and fortified defensive towers.